Synthesis of CdS/CoP hollow nanocages with improved photocatalytic water splitting performance for hydrogen evolution. Issue 6 (December 2021) - Zou, Yangyang; Guo, Changyan; Cao, Xianglei; Zhang, Liugen; Chen, Tingxiang; Guo, Cheng; Wang, Jide
Abstract: Photocatalysts with hollow structure have obvious advantages in photocatalytic hydrogen production. Herein, CoP was modified on the surface of CdS by sacrificial template method to prepare CdS/CoP composite photocatalyst with hollow structures. Compared with pure CdS, CdS/CoP nanocage has improved photocatalytic hydrogen production performance due to its hollow structure, excellent light absorption capacity, and electron-hole pair separation and transfer efficiency. The hydrogen production rate of CdS/CoP can reach to 15.74 mmol g −1 h −1, which is about 9 times than that of pure CdS. It is found that the formation of a p-n heterojunction between CdS and CoP is the key factor to improve the photocatalytic performance of the composites. This study provides a simple strategy for the construction of more hollow nanocomposite catalysts with excellent photocatalytic performance. Graphical Abstract: ga1 Highlights: CdS/CoP hollow cage was prepared by using PBA as sacrificial template. The H2 evolution rate of CdS/CoP is about 9 times higher than that of CdS. This method can construct the p-n heterostructure between CdS and CoP. The p-n heterostructure is favorable for the separation and transfer of electron-hole pair.